Cinemeducation: using film as an educational tool in mental health services. (March 2014) - Gorring, Helene; Loy, John; Spring, Hannah
Abstract This feature looks at the benefits of using film as an educational tool for mental health. In particular, it presents two case studies outlining how two health library services successfully implemented film clubs for the purposes of teaching and learning for mental health. H.S.